Application of field modeling and determination of parameters in electrical engineering education. Issue 5 (17th August 2018) - Iatcheva, Ilona
Abstract : Purpose: This paper aims to present application of electromagnetic field (EMF) modeling in the educational process of electrical engineering study. Special attention has been paid to determination of specific parameters and characteristics as a function of device design. The aim is to introduce to the students the great opportunities for study and optimization of system behavior, based on the modeling of EMF distribution. Design/methodology/approach: Illustrative examples have been considered, in which the students have to model the EMF distribution in relatively simple devices, using both analytical field determination and finite element method (FEM) analysis. The task includes also the determination of capacitances, inductances, magnetic fluxes, energies and forces. The problem has to be solved for different values of geometry parameters and material properties of the device. Thus, students can examine specific relation between field distribution and changes of the design. Findings: The modeling of EMF distribution for different geometry and material properties allows determination of key factors, significantly influencing the behavior and processes in the studied device, which is the basic element in the computer-aided design systems and it can be used in subsequent system optimization. Practical implications: The wide possibilities and advantages of the FEM simulations have been demonstrated in the modeling of EMF distribution and obtaining of device parameters. It enables students to significantly improve their knowledge in EMF theory and helps the future engineers to estimate the great advantages and possibilities for optimal device designing, which offer them the numerical simulation of electromagnetic processes. Originality/value: This work illustrates possibilities, advantages and many years of author's experience in application of EMF modeling in the teaching process in the study of electrical engineering specialties. The work problems presented have been solved analytically and on the basis of computer FEM simulations, which allows comparison of the opportunities and necessary efforts, offered by both kinds of methods.